Instituições de ensino superior e responsabilidade social: um estudo sobre as representações de lideranças da educação superior brasileira - Rosetto, Marcia Regina Chrispim Alvares (2011)
The history of personal and professional life of this researcher wove the problem that led to the guiding question of this research: What s the meaning of the concept from "Social Responsibility for leaders who represent the Brazilian Higher Education"? From this essay, the main hypothesis has been that the lack of precision in conceptual terms, in the law of SINAE, on what would be the social responsibility of higher education has generated a theoretical and conceptual confusion and also in practice, making of it a polysemic term for the main leaders of the Brazilian Higher Education, unleashing their immediate relation to the implementation of social projects like the prevailing trend in the business world. The methodological approach used in search for the answer to the question announced makes use of a grounding of qualitative research, with some allowance of quantitative research; of bibliographic and documentary research and field research. As a strategy for data collection techniques were used for observation techniques, questionnaire and reflexive interviews. This research aims to join the discussions on the concept of Social Responsibility of Institutions of Higher Education and grants to help with possible proposals for theoretical and practical policy on the subject cited. To do so, it elects as individuals surveyed representatives the Presidents of Associations, Councils, Forums and the Brazilian Higher Education Unions and Leaderships from Federal, State, Community and Private Universities, and from the Ethos Institute. Thereby, it has been investigating the representations of these leaderships on the issue in question, from the Law of SINAES. First, however, it deciphers the concepts related to the subject; emphasizes principles and assumptions based on authors such as ANASTASIOU, BRITO, CALDERÓN, CHAUÍ, CUNHA, DIAS SOBRINHO, DOWBOR, FÁVERO, FREIRE, PIMENTA, RISTOFF, SAVIANI, SEN, TEIXEIRA, it also analyzes the transformations that have occurred throughout the history, with the educational institutions of higher education in Brazil, seeking for the genesis and the evolution of the concept in focus, as well as practical experiences